Blood transfusion. (April 2021) - Booth, Catherine; Allard, Shubha; Robinson, Susan
Abstract: The term 'blood transfusion' refers to therapeutic use of whole blood or its components (red cells, platelets, fresh frozen plasma, cryoprecipitate). Careful donor selection and stringent testing by the blood service is required to ensure a safe blood supply. Blood transfusion can be life-saving. However, donated blood is a limited resource, and hospital blood transfusion practice must focus on ensuring safe and appropriate use. Patient blood management is an evidence-based multidisciplinary approach aimed at optimizing the care of patients who might need transfusion, to reduce avoidable use of blood components. Clinical transfusion guidelines are essential, supported by education and training with regular practice audits. To minimize errors, particular emphasis must be placed on accurate patient identification from the initial blood sample, through laboratory testing and transfer of blood to clinical areas, to the final bedside check before transfusion. The reporting and monitoring of adverse events via national haemovigilance schemes has highlighted key areas for action and improved transfusion safety. Transfusion medicine must be practised within a strict regulatory framework; the Blood Safety and Quality Regulations 2005 based on European Union blood directives have had particularly far-reaching implications for UK Blood Services and hospital transfusion laboratories.